Relationship of systemic pentraxin-3 values with coronary plaque components on optical coherence tomography and post-percutaneous coronary intervention outcomes in patients with stable angina pectoris. (January 2020) - Kimura, Shigeki; Sugiyama, Tomoyo; Hishikari, Keiichi; Nakagama, Shun; Nakamura, Shun; Misawa, Toru; Mizusawa, Masafumi; Hayasaka, Kazuto; Yamakami, Yosuke; Sagawa, Yuichiro; Kojima, Keisuke; Ohtani, Hirofumi; et al.
Abstract: Background and aims: Elevated pentraxin-3 (PTX3) values are associated with vulnerable plaque existence and poor outcomes in acute coronary syndrome patients. The clinical significance of PTX3 values in stable angina pectoris (SAP) patients is, however, undetermined. We investigated the relationship of systemic PTX3 values and coronary plaque components and post-percutaneous coronary intervention (PCI) outcomes in SAP patients. Methods: We included 93 consecutive de-novo lesions in 93 SAP patients with a normal pre-PCI high-sensitivity cardiac troponin-T (<0.014 ng/mL), undergoing pre- and post-PCI optical coherence tomography (OCT). Systemic PTX3 values were obtained immediately pre- and post-PCI, at 24-h and 9-month post-PCI. Results: Peak post-PCI PTX3 values correlated with thinnest fibrous cap thickness (r = −0.23, p = 0.03) and lipid length (r = 0.24, p = 0.03), and were higher in patients with lesions having OCT-derived thin-cap fibroatheroma (6.67 (3.19–7.33) vs. 3.13 (2.34–4.11) ng/mL, p = 0.04) and post-stenting irregular tissue protrusion (4.76 (3.31–6.80) vs. 2.98 (2.23–4.06) ng/mL, p = 0.003) than in those without. At 9-month follow-up, cardiac event-free survival was poorer in patients with a peak post-PCI PTX3 value ≥ 4.08 ng/mL (upper tertile) (log-rank test χ 2 = 9.0; p = 0.003). Multivariate Cox regression analysis showed a peak post-PCI PTX3 value ≥ 4.08 ng/mL as an independent predictor of MACE (hazard ratio, 3.915; 95% CI, 1.129–13.583; p = 0.03). Conclusions: Peak post-PCI PTX3 values correlated with pre-PCI plaque characteristics and post-PCI outcomes, providing a good prognostic factor of outcomes in SAP patients undergoing elective PCI. Graphical abstract: Image 1 Highlights: The clinical significance of pentraxin-3 (PTX3) values in stable angina pectoris (SAP) patients remains undetermined. We assessed the impact of PTX3 values on coronary plaques and post-percutaneous coronary intervention (PCI) outcomes. Peak post-PCI PTX3 values was related to thin-cap fibroatheroma (TCFA) and post-PCI irregular protrusion. Peak post-PCI PTX3 was an independent predictor of major adverse cardiac events (MACE) after PCI in SAP patients.